Bay Area Women's Coalition Newsletter October 1976 (1976)
This October 1976 newsletter from the Bay Area Women's Coalition outlines upcoming meetings, political forums, and fundraising activities, including a Board of Education candidates forum and discussion of co-sponsoring a fundraiser with Bella Abzug. It reports recent endorsements of local and state candidates—among them Jane Tolmach for State Assembly—and calls for volunteer support for endorsed campaigns. The newsletter also summarizes State and National Women's Political Caucus steering committee activities, including fundraising for ERA ratification, candidate support allocations, and selection of San Jose as the 1977 national convention site. Additional announcements promote women-centered events, political rallies, policy hearings, and conferences focused on education, employment, health, and economic survival for women.